Preparation and performance evaluation of non-foaming styrene-acrylic latex for cementing slurry - Shenglai Guo; Ming Li; Sihe Li; Jiaxin Zhao; Yuhuan Bu; Huajie Liu; Yindong Wang (Royal Society Open Science, 2023)
The latex used conventionally for oil-well cementing can lead to serious foaming issues in the cement slurry, which not only affects the accurate measurement of the density of the latex-containing cement slurry, but also is detrimental to cementing construction. A large amount of a foam stabilizer used for latex preparation is mainly responsible for foaming of the latex-containing cement slurry. In this study, soap-free emulsion polymerization was conducted using 2-acrylamido-2-methylpropanesulfonic acid (AMPS), styrene (St), and butyl acrylate (BA) as the reaction monomers and the effects of the AMPS dosage, monomer ratio, reaction temperature and stirring speed on the performance of the latex were investigated. The optimum synthesis conditions included a 30% monomer concentration, an St : BA : AMPS monomer ratio of 5 : 4 : 6, a synthesis temperature of 85°C, a stirring speed of 400 r.p.m. and 1.5% of the initiator. As-prepared latex exhibited good filtration loss control, excellent freeze–thaw stability, and extremely low foaming of the cement slurry with the added latex, which was extremely beneficial for on-site cementing construction.